ANALISA STRATEGI PROMOSI USAHA PISANG KEMBUNG "SWEET BANANA" DI KOTA AMBON - Wa Ode Intan Muliyani Abdul Latif; Wendy Souisa; Sherly Rutumalessy (Jurnal Administrasi Terapan, 2026)
MSMEs play a crucial role in economic growth, including the ever-expanding culinary sector. However, MSMEs often face challenges in implementing effective promotional strategies. This study examines the promotion of the Sweet Banana puffed banana business, a small-scale business that relies solely on WhatsApp, personal Facebook, and word-of-mouth. The main problem is suboptimal promotion, resulting in stagnant sales despite the product's distinctive flavor and popular topping variety. The purpose of this study is to analyze the promotional strategies employed to increase sales turnover. The study employed a descriptive qualitative method, collecting data through interviews and observations. The data obtained were then analyzed using a promotional mix approach. The results show that the "Sweet Banana" business utilizes only simple personal selling and direct marketing, while other elements such as advertising, sales promotions, and public relations are underutilized. Consumer responses indicate that promotions are unattractive, inconsistent, and often lack comprehensive information. The conclusion of this study is that the main weakness of the "Sweet Banana" business lies not in the product or price, but in its suboptimal promotional strategy. To increase sales, business owners need to conduct more targeted promotions through social media business accounts, a regular promotional schedule, engaging content, and utilizing simple sales promotion strategies. With these steps, businesses have the opportunity to expand their market, increase sales volume, and strengthen their position among consumers. Keywords: Promotion Strategy